Impact of clozapine monotherapy on gut microbiota and metabolism in people with schizophrenia - Yin, Feiyan; Shi, Zhidao; Ma, Xiquan; Ding, Kai; Zhang, Yuan; Ma, Sha (Frontiers in Microbiology, 2023)
Background Clozapine is considered one of the most effective antipsychotic drugs, but it is most likely to cause metabolic abnormalities. Researchers have studied the causes of metabolic abnormalities caused by clozapine from multiple perspectives, but the reasons remain unclear. Purpose Characterize the gut microbiota of people with schizophrenia taking clozapine, exploring the association between gut microbiota and glucose lipid metabolic markers in schizophrenia patients taking clozapine. Research design Sixty-one long-term inpatients with schizophrenia in clozapine monotherapy were selected as study subjects. We got four subgroups by sex and the presence of metabolic syndrome. Data analysis 16s analysis technology was applied at the genus level to determine the classification of gut microbiota. Then we compared the characteristics of gut microbiota and the association of gut microbiota with glucose lipid metabolic markers in each group. Findings We found differences in the diversity of gut microbiota among groups. The association between gut microbiota and glucose lipid metabolic markers was complicated. Gender was an important differentiating factor. Oscillibacter has a low abundance. However, it was the only genus associated with glycemic or lipids in each group. Among metabolic syndromes, Gemmiger was positively correlated with most lipids in females but negatively correlated in males, showing gender differences. In female non-metabolic syndromes, Bifidobacterium lost its probiotic character; instead, showing pathogenicity, which has strong positive correlations with fasting blood glucose and low-density lipoprotein but negative correlations with Apolipoprotein A1. Maybe schizophrenia, taking clozapine, and gender factors influenced the gut microbiota, which complicated our findings. The significance of the results remains to be determined by in-depth studies.